2024
DOI: 10.24198/pjd.vol35no3.49071
|View full text |Cite
|
Sign up to set email alerts
|

The value of imbibition and syneresis for dental impression on red seaweed: a laboratory experiment

Didin Erma Indahyani,
Izzata Barid,
Priska Amelia Anggraeni

Abstract: Introduction: Alginate is a type of elastic dental impression, which is an irreversible hydrocolloid. The main components in sodium alginate can be obtained naturally through the extraction process from seaweed (Kappaphycus alvarezii). Several physical characteristics must be fulfilled by dental impressions, such as dimensional stability related to imbibition and syneresis. ANSI/ADA specification No.18 regarding the maximum permitted change in alginate impression materials may not exceed 0.5%. This research ai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…This is particularly difficult to achieve in situations where the dental laboratory is not in the same facility as the dental practice. The low dimensional stability of alginate is produced by the phenomena of imbibition and syneresis [44,45]. Also, Peutzfeld et al observed that out of all the studied materials, alginate had the lowest accuracy [46].…”
Section: Discussion Regarding the Impression Techniquementioning
confidence: 99%
“…This is particularly difficult to achieve in situations where the dental laboratory is not in the same facility as the dental practice. The low dimensional stability of alginate is produced by the phenomena of imbibition and syneresis [44,45]. Also, Peutzfeld et al observed that out of all the studied materials, alginate had the lowest accuracy [46].…”
Section: Discussion Regarding the Impression Techniquementioning
confidence: 99%